Therapeutic efficacy and safety of mesenchymal stem cells transplantation for patients with liver failure: a systematic review and meta-analysis - Qi, Feng; Jiang, Zongze; Gong, Jianping; Feng, Yi (International Surgery Journal, 2021)
The aim was to pool the present clinical studies to assess the therapeutic efficacy and safety of mesenchymal stem cell transplantation (MSCT) compared with traditional supportive treatment (TST) for patients with liver failure. Publications were searched to identify relevant clinical trials in which LF patients accepted mesenchymal stem cell transplantation from the online databases of PUBMED, EMBASE, and Cochrane Library up to June 2020. Then, the short-term outcomes of 6 months, including models of end-stage liver disease (MELD) score, total bilirubin (TBIL), albumin (ALB), prothrombin activity (PTA), alanine aminotransferase (ALT), prothrombin time (PT) and cumulative survival rate were enrolled in a meta-analysis. In total, 446 patients, reported on 2 randomized controlled trials (RCTs) and 4 non-randomized trials, were included. Compared with TST, MSCT was associated with a faster decline of MELD score at 2-, 4-, 12- and 24-week, greater improvement of ALT levels at1-, 4-, 24-week, significant increase of ALB levels at 4-,12-week and remarkable raise of PTA levels at 12-, 24-week, while PT levels changed greatly at 4-week and TBIL levels observably decreased at 4-week. The cumulative survival rate of MSCT was shown significant difference at 12-week. There were no serious complications and HCC occurred after MSCT. This study suggests MSCT may be a more effective and safe strategy than TST to improve liver function parameters and alleviate liver damage in LF patients during the short-term duration of 6 months. However, more multi-center, large-scale RCTs are needed.